Characteristics of Thermally Sprayed WC Cermet Coating under Lubricated Rolling with Sliding Contact (Journal of Mechanical Engineering, 2008)
The characteristics of thermally sprayed WC-Cr-Ni cermet coating under lubricated rolling with sliding contact condition were examined experimentally. Experiments were performed using a two-roller testing machine. The coating was formed onto the blasted or ground roller specimens made of thermally refined carbon steel or induction hardened carbon steel by high energy type flame spraying (Hi-HVOF). A mirror-like finished cermet coated steel roller was mated with a non-coated carburized hardened steel roller. In the case of thermally refined steel substrate and for the mating surface roughness Rmax=0.1 Î¼m, coating on the ground substrate showed lower durability than that on the blasted substrate. For the mating surface roughness Rmax=3.0 Î¼m, coating on the ground substrate showed an extremely short life as compared with that on the blasted substrate. In general, durability of cermet coating was greatly increased due to the increase in the coating thickness. In the case of induction hardened steel substrate, coating on the blasted or ground substrate showed high durability for both Rmax=0.1 Î¼m and 3.0 Î¼m. Coefficient of friction and oil film thickness were markedly influenced by the mating surface roughness but these were hardly affected by the substrate material. In addition, depending on the mating surface roughness, significant differences in the surface roughness of coated roller and depth of flaking on the coated roller were found. Keywords: WC cermet, Mating surface roughness, Substrate surface kind, Substrate materialdoi:10.3329/jme.v37i0.815Journal of Mechanical Engineering Vol.37 June 2007, pp.18-23